Effect of Employee Development and Interpersonal Communication on Employee Performance (Case Study on Employees of PT Astra Agro Lestari) - Prihambodo, Refi Radhea; Rabbani, Ziddan Fahreri; Maulidiansyah, Rafiq; Saputra, Guntur Ari; Dirgantara, Muhammad Arya (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research examines the influence of employee development and communication on employee performance at PT Astra Agro Lestari, a company operating in the plantation and agro-industry sectors. This research uses quantitative methods with data measurement using the Liekert scale. Data was collected through questionnaires distributed to employees at various levels. Data analysis was carried out using the SPSS application to measure the relationship between employee development variables, interpersonal communication, and employee performance. The research results show a positive and significant influence between employee development variables (x1) and interpersonal communication (x2) on employee performance (y)